Investigation of the electric drive system of the lifting unit with parallel coordinate correction - Reshetnyak Sergey (EDP Sciences, 2021)
In the presented publication, the issues of improving the energy efficiency of the electric drive system, in relation to mine lifting installations, are considered. A block diagram of the electric drive system of a mine lifting installation with parallel coordinate correction is considered, as well as a mathematical description of the presented system. It should be noted that the conducted research will significantly affect the improvement of the level of safety and accident-free operation of the mine lifting plant, which will increase the competitiveness of coal mining by underground method.